Effect of Dapagliflozin on hemoglobin level in heart failure patients with chronic kidney disease and/or diabetes - A. Obeed, Ahmed; A. AL-Kinani, Tahseen; Ibrahim AL- Qadhi , Huda (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Heart failure is a complex clinical syndrome caused by any functional or structural cardiac disease that reduces the ventricle’s ability to fill or pump blood. Anemia is frequent in patient with heart failure and is associated with deterioration through the activation of neuro-hormonal pathways. Dapagliflozin is a selective and reversible inhibitor of Sodium-glucose co-transporter-2 (SGLT2). Dapagliflozin increases hemoglobin level through different mechanisms such increasing plasma concentration by diuresis or increasing Erythropoietin synthesis. Objective: To evaluate the effect of additional dapagliflozin into conventional therapy on hemoglobin in heart failure patients with chronic kidney disease (CKD) with or without diabetes mellitus DM. Patients and Methods: This was prospective clinical study conducted at medical wards at Nasiriya Heart Center during the period from the 1st November / 2021 to the end of July / 2022. The research was conduct on 120 participants with heart failure and renal impairment. The patients were divided into two groups. The first group included 60 patients who were administered dapagliflozin in addition to conventional medication and the other group consisted of 60 patients who received only conventional therapy. Both groups were matched regarding socio-demographic characteristics. Hemoglobin concentration, was recorded on day 1 as a baseline visit then followed up after four months. Results: Before treatment there were no significant differences in sociodemographic and clinical parameters between the two groups. In the dapagliflozin group, hemoglobin level was significantly higher than pre-therapeutic level (12.53 g/L vs 11.85 g/L, P= 0.016).patients in the control group had significantly lower mean level of hemoglobin after treatment compared to baseline level (11.88 g/L vs 12.56 g/L, P= 0.001). Conclusion: The study shows that dapagliflozin increases the concentration of hemoglobin and correct anemia in patients with heart failure with CKD compared to the control group.